2011
DOI: 10.1111/j.1442-2018.2011.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Cypriot nurses with Standard Precautions to avoid exposure to pathogens

Abstract: Standard Precautions have been introduced as a means to protect health professionals from exposure to pathogens. This study examines the extent of Cypriot nurses' compliance with the main aspects of Standard Precautions and explores the possible associations with the nurses' characteristics. Self-completed questionnaires that examined the frequency of the implementation of Standard Precautions were distributed to a convenience sample of 668 nurses.The response rate was 89.37%.The results showed inadequate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 35 publications
5
42
1
4
Order By: Relevance
“…Other professional constraints included a lack of cultural competency while others expressed cultural insensitivity. This is important considering other studies involving students have also reported observations where nurses appear reluctant to provide care to ethnic minorities [48] [49] and where a lack of cultural competence creates barriers to learning about caring [44] as found in our findings.…”
Section: Professional Constraintscontrasting
confidence: 30%
“…Other professional constraints included a lack of cultural competency while others expressed cultural insensitivity. This is important considering other studies involving students have also reported observations where nurses appear reluctant to provide care to ethnic minorities [48] [49] and where a lack of cultural competence creates barriers to learning about caring [44] as found in our findings.…”
Section: Professional Constraintscontrasting
confidence: 30%
“…In other international studies, low knowledge and professional adhesion to SP were also observed (15)(16)(25)(26)(27) , indicating that there are still differences in participation rates between developed countries and developing ones.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main obstacles identified by nurses for non-adherence to SP corresponds to an emergency situation, one in which the professional considers patient care first, and then their own safety (15) , situations that are also experienced by professionals in mental institutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, one needs to tune into one's experiences with uncertainty, anger, sadness, joy, love, etc. which creates the capacity for becoming sensitive to another's emotional state and needs [55]. Our carers' described the necessity of "tuning in" to the other, as also vital to caring, as confirmed by others [42].…”
Section: Sensitive To Selfmentioning
confidence: 91%